Discontinued Splenogonadal Fusion and Bilateral Empty Scrotum in an 18-Month-Old Boy - Abokrecha, Ahmed; Almatrfi, Ameera (European Journal of Pediatric Surgery Reports, 2017)
Splenogonadal fusion is a rare benign congenital anomaly defined as the presence of splenic tissue adherent to gonads. It was first described in 1883 by Bostroem, a German pathologist. We present a case of an 18-month-old boy who was referred as a case of bilateral empty scrotum since birth. During routine laparoscopic exploration, right vas deferens and testicular vessels were entering the right internal inguinal ring so right inguinal exploration was done, which revealed blind ending vas deferens and testicular vessels and the left testis was found intra-abdominally near the left internal ring with a mass on its upper pole. Wedge biopsy was taken from the upper pole of the testicle (site of the mass) for tissue diagnosis followed by orchidopexy. Histology showed splenic tissue. Although splenogonadal fusion is a rare condition, surgeons should be aware of this rare disease entity to avoid unnecessary aggressive interventions such as orchiectomy.
Keywords: Bilateral Empty Scrotum; orchidopexy; discontinued splenogonadal fusion